Contribuição ao estudo de compósitos de espuma rígida de poliuretana reforçada com resíduos de celulose - Merces Coelho da Silva (2008)
This work presents the study of an industrial reject obtained during the production of pulp whitened cellulose aiming its valorization as renewable material. The reject was mercerized and both non-mercerized and treated materials were characterized regarding chemical composition, structural, thermal and morphological properties. Fourier transform Infrared Spectroscopy, X-ray diffraction (DRX), Thermogravimetry (TG), Scannig Electronic Microscopy (MEV) and mechanical behavior by universal testing machine and Zero-Spain have been investigated. Composites of rigid polyurethane foam and industrial reject both non treated and mercerized were prepared. The foam densities were tested according to ASTM D 1622; mechanical properties characterization was carried out by determining resistance to compression at 10% deformation according to ASTM D 1621-73; and tensile resistance was obtained using DMA (Dynamical Mechanical Analysis). Thermal conductivity was characterized by following ASTM C 177-97. The results showed that the industrial reject can be classified as a fibrous material of good quality, which may be used as an alternative renewable source. The RDC fiber introduction in the processing of the foam did not change the foam thermal stability. The foam composites with the no mercerized fiber presented thermal conductivity values smaller than the matrix foam. The biodegradation study of the composite foam with 16% m/m cellulose reject compared to the matrix showed indications of susceptibility to biodegradation due to the vegetable fiber.